2018
DOI: 10.1097/iop.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Medial Buttressing in Orbital Blowout Fractures

Abstract: Endoscopic ethmoidectomy in fresh cadavers reduces impact energy necessary to induce orbital fracture and increases the prevalence of medial wall involvement. Clinicians may wish to counsel patients undergoing endoscopic sinus surgery about these relative risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The absence of detailed anatomy of the ethmoid is a limit of our model. Ramesh et al [26] proved that ethmoidectomy on post mortem human subject reduces the impact energy necessary to induce orbital fractures and increases the prevalence of the medial wall's involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of detailed anatomy of the ethmoid is a limit of our model. Ramesh et al [26] proved that ethmoidectomy on post mortem human subject reduces the impact energy necessary to induce orbital fractures and increases the prevalence of the medial wall's involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Ramesh et al performed a similar study to the one presented here and found almost 50% less force was required to cause an orbital fracture after ethmoidectomy. They also found that all specimens with an ethmoidectomy had medial fractures versus 20% in controls [8].…”
Section: Discussionmentioning
confidence: 94%
“…The applied pressure and energy may also be significantly lower. In the case of repeated trauma to the orbit, surgical procedures in the nasopharyngeal region (ethmoidectomy), or cancer in the vicinity associated with atrophy of the orbital skeleton, the pressure and energy needed can be significantly lower, as seen in a report by Ramesh and Bokman, who observed a pressure of only 11.8 mm Hg and an energy of 2.14 J [32]. Based on the above, it is clear that a relatively low-energy impact can fracture the orbital walls, but in order to push the eye outside the orbit, it is necessary to apply a repeated force of higher intensity, as was the case with the victim in our report.…”
Section: Discussionmentioning
confidence: 99%